NETNOGRAPHIC STUDY ON THE NARRATIVE OF MARRIAGE AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA): OPPORTUNITIES AND CHALLENGES - Saehu, Rahmat; Syarifudin, Achmad; Adi Paramitha, Nurina; Hilmi, Farida (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
AbstractMarriage is related not only to the couple undergoing it but also to a process of accepting individuals as part of society, and therefore wedding planning often involves other extended parties. One of the discussions for couples and families is the location of the wedding. Even though the Office of Religious Affairs (KUA) has services, supervision, registration, and reporting of marriages, it has yet to become the preferred location for conducting marriage. The method used in this study is qualitative with a netnographic approach. The data used in this study came from Twitter which was taken (data crawling) using the netlytic.org application. As many as 20,000 tweet data were collected over two weeks, from January 26, 2023, to February 9, 2023. From 20,000 tweet data, it was successfully sorted up to 9,090 tweet data discussing marriage at KUA. The results showed that the normalization of marriage in the Office of Religious Affairs has opportunities and challenges. Opportunities for normalizing marriage at the KUA include Revitalization of KUA Services, Pandemic Conditions which are becoming momentum and Changes in the People's Mindset. Meanwhile, the challenges for normalizing marriage at the KUA include misperceptions about service procedures and fees, negative community stigma and views of previous generations. AbstrakPernikahan bukan hanya terkait pada pasangan yang menjalani melainkan sebuah proses pernerimaan individu-individu menjadi bagian dari masyarakat sehingga perencanaan pernikahan seringkali melibatkan pihak lain. Salah satu yang menjadi diskusi bagi pasangan dan keluarga yaitu lokasi dilaksanakannya pernikahan. Meskipun Kantor Urusan Agama (KUA) memiliki pelayanan, pengawasan, pencatatan dan pelaporan nikah sayangnya belum menjadi pilihan lokasi melakukan akad nikah. Metode yang digunakan dalam penelitian ini yaitu kualitatif dengan pendekatan netnografi. Data yang digunakan dalam penelitian ini berasal dari twitter yang diambil (data crawling) dengan menggunakan aplikasi netlytic.org. Sebanyak 20.000 data tweet berhasil dikumpulkan selama dua pekan yakni sejak tanggal 26 Januari 2023 sampai dengan 9 Februari 2023. Dari 20.000 data tweet berhasil dibersihkan hingga menjadi 9.090 data tweet yang membahas nikah di KUA. Hasil penelitian menunjukan bahwa normalisasi pencatataan pernikahan di dalam Kantor Urusan Agama memiliki peluang dan tantangan. Peluang normalisasi nikah di KUA antara lain; Revitalisasi Layanan KUA, Kondisi Pandemi yang menjadi momentum dan Perubahan Mindset masyarakat. Sedangkan tantangan bagi normalisasi nikah di KUA antara lain; Mispersepsi tetang prosedur dan biaya layanan, Stigma negatif masyarakat dan Pandangan Generasi Sebelumnya.